2017
DOI: 10.1097/sla.0000000000001993
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variation and Excessive Dosage of Opioid Prescriptions for Common General Surgical Procedures

Abstract: There is wide variability in opioid prescriptions for common general surgery procedures. In many cases excess pills are prescribed. Using our ideal number, surgeons can adequately treat postoperative pain and markedly decrease the number of opioids prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
680
4
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 768 publications
(710 citation statements)
references
References 16 publications
23
680
4
3
Order By: Relevance
“…Our findings of opioid over-prescription are similar to recent reports in other surgical cohorts 47 , including cesarean section. 8,9 However, few studies have examined whether individual patient factors predict outpatient opioid use.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings of opioid over-prescription are similar to recent reports in other surgical cohorts 47 , including cesarean section. 8,9 However, few studies have examined whether individual patient factors predict outpatient opioid use.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have found that most patients undergoing various surgical procedures 47 , including cesarean section 8,9 , are prescribed opioids in excess of what they use. Despite the era of personalized medicine, most studies did not investigate whether individual patient factors influence opioid use and postsurgical pain during the postoperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with current literature, the physician distribution graphs keep showing wide variation in opioid prescribing. 6 Physicians who are outside of the data boundaries of reasonable variation for standardised procedures as set by our hospitals pain specialists are easily identifiable.…”
Section: Fig 1 Distribution Of Surgeons By Number Of Opioid Pills Thementioning
confidence: 99%
“…A recent study in ERAS for colorectal surgery showed that despite a reduction in inpatient postoperative opioids as a result of consistent compliance with multimodal and regional analgesia, patients were just as likely to be prescribed opioids at hospital discharge. 18 These findings, described by others as well, were primarily attributed to systems-level failures in time-of-discharge communication, prescription practices, 4,19 and patient follow-up coordination.…”
mentioning
confidence: 89%